Role of two isothermal cylinders towards three-dimensional flow and melting of phase-change materials - Sameh E. Ahmed; Zahra S. Hafed; M.A. Mansour; Eman F. Mohamed; M.A.Y. Bakier (Case Studies in Thermal Engineering)
Recently, investigators focused on examining the melting of phase change materials (PCM) in regular two-dimensional or three-dimensional flow domains. At the same time, this topic still needs more study to get a better understanding of it. Also, such problems should be reported using the local thermal non-equilibrium (LTNE) model because the latent heat substances and the included porous elements have different temperatures. Therefore, this study examines the three-dimensional flow and melting process of phase change materials (PCM) within cubic enclosures filled with copper foam, using a local thermal non-equilibrium model (LTNE). The system includes two isothermal cylinders with different temperature conditions, varying distances, and radii, placed within the flow domain. The enthalpy-porosity approach is applied to model the PCM behavior, while the Brinkman-extended non-Darcy model accounts for high-velocity flow situations. A magnetic field is introduced to control the flow, with the Lorentz force acting opposite to gravity. The governing equations are solved using a home-developed code based on the finite volume method with the SIMPLE algorithm. Key parameters investigated include cylinder radii, Fourier number, Hartmann number, horizontal and vertical distances between cylinders, and Darcy number. The results are presented through streamlines, temperature distributions for fluid and solid phases, and profiles of the Nusselt number and average liquid fraction.